DETERMINANA PENANAMAN MODAL ASING : STUDI KASUS : PULAU JAWA TAHUN 2011-2020 - Rahajeng Dila Safitri (Pendidikan Ekonomi FPEB Universitas Pendidikan Indonesia, 2023)
The study aims to analyze the effect of the Gross Regional Domestic Product, Infrastructure, Minimum Wage and Openness on The Foreign Direct Investment. This research use secondary data, namely Gross regional Domestic Product, Infrastructure, Minimum Wage, Openness and Foreign Direct Investment in Java Island in 2011-2020. This research analysis method used a panel Cointegration. Based on the result of the analysis showed that Gross Regional Domestic Product has a positive effect on the Foreign Direct Investment, Infrastructure has a positive effect on the Foreign Direct Investment, Minimum Wage has no effect on the Foreign Direct Investment, Openness has a positive and effect on the Foreign Direct Investment.